Robots, the Alzheimer patient, and the GDPR: Policy and privacy considerations for the use of robots in care, treatment, and diagnosis: Health services research / Policy and plans. (7th December 2020) - Pierce, Robin
Abstract: Background: Several types of robots are currently being designed and introduced to address the needs of dementia patients at various stages of the disease progression. Robots hold the potential to fill some of the gap left by nursing and other staff shortages. In recent years, smaller, lighter, and less expensive robots have entered the market. Moreover, more sophisticated robots that combine functions of "companionship" with other care functions are becoming available. Increasingly, these robots contain sensors that serve a range of monitoring functions that can alert caregivers, neighbors, and clinical staff to phenomenon that may signal the need for attention or follow‐up. Robots that employ AI and thus, through the processing and refining of outputs, are able to "evolve" to better interact with the patient. Methods: A survey of therapeutic, social, and social care robots were assessed to identify functions, processes, and designed purpose. A legal and ethical analysis identified data protection and privacy issues that arise in the deployment of these robots. This analysis is performed within the context of queries about the appropriateness of certain types of task‐shifting to robotics in dementia care and treatment. Result: In performing monitoring functions for clinical or safety purposes, as well as "intelligent" companionship, these robots necessarily collect a range of data. Given that ever‐increasing phenomena, including behavioral, physiological, verbal, emotional, are recognized as being informative of a dementia‐relevant event (e.g. diagnosis, progression), this processing of environmental and personal information can be helpful to clinical staff and enhance caregiving. Yet, this data‐driven technology invokes consideration of privacy concerns, particularly in view of the General Data Protection Regulation in the EU. Concerns about the collection of sensitive (health) data of the patients and others in a shared environment, e.g. a nursing home, must comport with legal and ethical requirements. Conclusion: Beyond data protection concerns, the broader issue of privacy is triggered by these technologies, forcing questions about optimal and ethical care, monitoring of the Alzheimer's patient, and challenges for "task‐shifting". This paper explores privacy and data protection issues in the shifting of certain tasks, functions, and responsibilities to therapeutic robotics, and addresses related legal and ethical considerations.